Kekuatan Geser Panel Kayu Vertikal Dengan Perkuatan Single Bracing Tulangan Baja Akibat Pembebanan Siklik - Fanny Monika (Semesta Teknika, 2016)
Panels  in wooden construction serve as walls as well as providing structural lateral  resistance  against  earthquake  if  designed well. Panel materials  consist of frames with  sheathings  such  as  Plywood  or Oriented Strand Board(OSB)  connected  to  wooden  frames with nails as connectors. Lateral force of the panels can be increased, for example by adding diagonal rods/bracings to the frames. In this study a wooden  panel which was Sengon wooden panel connected to Laminated Veneer Lumber(LVL) wooden panel with CN 50 nails with  a diameter of 2,8 mm and  the distance between  the nails was 240 mm with plain  steel  reinforcement  single bracing with a diameter of 8 mm in pull position using corner plate as a connector between bracing and LVL wooden panel. Cyclic  test had 20%Δy,  40%Δy,  60%Δy  deformation controls  and  loaded with monotonic  until wooden panels collapsed. The  results of cyclic  test  in  stable  condition  60%Δy had equivalent viscous damping ratio values of 8,324%.  Failures  in  panels  often  happened  to  connecting  nails,  corner  plates,  and steel  bracings. The  types  of  failure were Nail  Pull-Through  of  Sheathing,  Pull-Through  Sheathing  Failures,  Mudsill  Failure,  buckling  on  corner  plates,  and buckling on steel bracings